Penerapan Model Pembelajaran Berbasis Proyek Sebagai Solusi Keterbatasan Sarana Dan Kompetensi Guru Di Sekolah Wilayah Suburban Studi Kasus Smkn 1 Cileungsi - Siregar, Julinda; Hidayanti, Leny; Lestari, Rina Diana; Atiyani; Adriyadi, Rudy; Naryani, Ani; Pratiwi, Rizka Juniarti (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This study aims to analyze the implementation of the Project-Based Learning (PjBL) model as a solution to limited resources and teacher competencies in suburban schools, using a case study of SMK Negeri 1 Cileungsi. The background of this research stems from the challenges faced by schools in suburban areas, where limited facilities and varying levels of teacher competence often hinder the implementation of effective and innovative learning. The research employed a descriptive qualitative approach, with data collected through observations, interviews, and the analysis of learning documents. The results indicate that the implementation of the PjBL model can enhance students’ active engagement in the learning process, strengthen collaboration among learners, and foster critical and creative thinking skills, despite resource limitations. Furthermore, teachers demonstrated improved pedagogical competence through direct experience in designing and implementing project-based learning activities. The successful implementation of this model is strongly influenced by collaboration among educators, support from school management, and teachers’ readiness to adopt project-based learning strategies. Therefore, this study recommends the implementation of PjBL as a strategic alternative to address limited educational resources in suburban areas. The practical implications of this research are expected to serve as a reference for other schools facing similar conditions, enabling them to create learning environments that are more contextual, innovative, and oriented toward 21st-century competencies.